Kandungan Antosianin dan Karakteristik Sensori Kue Pia Ubi Ungu - Duniaji, Agus Selamet; Jambe, I A.A. Anom; Puspawati, Ni Nyoman (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 3 No 1 (2018)DO - 10.24843/JITPA.2018.v03.i01.p04, 2018)
The aim of this research is to know the anthocyanin content  and Characteristics of Pia cake of Purple Sweet Potato as well as The Indonesia National standards (SNI) and has sensory properties are acceptable and preferred by consumers. Specific objectives of this study was to determine the effect of the addition of purple sweet potato anthocyanin content, moisture content and texture of the Pia Purple Sweet Potato. This research was carried out to know the substitution of purple sweet potato and wheat such as (100% : O%= T0), (95% : 5%,=T1) (90% : 10%=T2), (85 %: 15%=T3), (80% : 20%=T4 and 75% : 25%=T5). Experiments were performed with 3 repetitions. Parameters measured were anthocyanin content (Apriantono et al., 1989), the water content with the oven method (Selamet Sudarmaji, 1997) and sensory test with Scoring test. The research of results showed that the addition concentration of purple sweet potato 10% give the best results pia cake with the characteristics of the water content of 29.10%, anthocyanin 2.87%, texture preferred (score 6:06), color preferred (6:20) and the flavor is preferred (score 6:53)